METHODOLOGY OF DEVELOPING PHYSICAL QUALITIES IN STUDENTS - Suyunov Odiljon Orif o‘g‘li (American Journals, 2025)
This article describes the structural basis of the development of physical qualities in relation to progressive morphological and biochemical changes in the musculoskeletal system, central and peripheral nervous systems, and internal organs, and the methodology for educating the physical qualities of high-grade students.
Keywords: Physical qualities, musculoskeletal system, education of physical qualities, general endurance.